2019
DOI: 10.12688/f1000research.19190.1
|View full text |Cite
|
Sign up to set email alerts
|

Advances in understanding the role of adipose tissue and mitochondrial oxidative stress in Trypanosoma cruzi infection

Abstract: Trypanosoma cruzi, the etiologic agent of Chagas disease, causes a latent infection that results in cardiomyopathy. Infection with this pathogen is a major socio-economic burden in areas of endemic infection throughout Latin America. The development of chagasic cardiomyopathy is dependent on the persistence of this parasite in host tissues. Pathogenesis of this cardiomyopathy is multifactorial and research indicates that it includes microvascular dysfunction, immune responses to host and parasite antigens, and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 38 publications
0
7
0
Order By: Relevance
“…CD has been tightly linked to alterations in metabolic substrate utilization and impairments of mitochondrial oxidative capacity and endoplasmic reticulum functions in the hearts (22,33,(66)(67)(68). It is known that patients with heart disease exhibit a shift from fatty acid oxidation toward greater dependance on glucose as a source for cellular energy adenosine triphosphate (ATP) (69).…”
Section: Discussionmentioning
confidence: 99%
“…CD has been tightly linked to alterations in metabolic substrate utilization and impairments of mitochondrial oxidative capacity and endoplasmic reticulum functions in the hearts (22,33,(66)(67)(68). It is known that patients with heart disease exhibit a shift from fatty acid oxidation toward greater dependance on glucose as a source for cellular energy adenosine triphosphate (ATP) (69).…”
Section: Discussionmentioning
confidence: 99%
“…The role of adipose tissue in the pathogenesis of infectious diseases has increased attention in recent years (41)(42)(43)(44)(45). Adipose tissue constitutes a nutritionally rich organ for the survival of pathogens such as Mycobacterium tuberculosis, Trypanosoma cruzi, HIV, among others (9,46,47).…”
Section: Discussionmentioning
confidence: 99%
“…(13) Growing evidence indicates that parasite persistence is central to the disease by driving the immune response, tissue destruction and chronic inflammation. However, T. cruzi antigens remain scarce and are not always associated with inflammatory foci in the myocardium (14) . The persistence of the parasite in tissues associated with poorly adapted homeostatic mechanisms, such as the oxidative/ antioxidative and proinflammatory/anti-inflammatory processes associated with the dysregulation of the immune response, seems to be essential for the onset and progression of Chagas heart disease.…”
Section: Pathogenesis Of Chronic Chagas Heart Disease: New Horizonsmentioning
confidence: 99%
“…(11,12) Recently, studies using hypercaloric diets in animal models have shown an increase in the parasitic load in adipose tissue with a consequent reduction in parasitaemia in cardiac tissue, suggesting that adipose tissue could act as a reservoir for later migration of the parasite to other organs and a possible protective role of adipose tissue in the evolution of chronic Chagas cardiomyopathy. (13,14) The discrepancy between the severity of tissue damage and parasite load has led to the suggestion that the inflammatory immune response of the host is the most important determinant of progression. (13) The balance between immune-mediated parasite containment and damaging inflammation of host tissues likely determines the course of disease.…”
Section: Pathogenesis Of Chronic Chagas Heart Disease: New Horizonsmentioning
confidence: 99%